Mesenchymal stem cells: Emerging concepts and recent advances in their roles in organismal homeostasis and therapy - Liu, Peisheng; An, Yongqian; Zhu, Ting; Tang, Siyuan; Huang, Xiaoyao; Li, Shijie; Fu, Fei; Chen, Ji; Xuan, Kun (Frontiers in Cellular and Infection Microbiology, 2023)
Stem cells play a crucial role in re-establishing homeostasis in the body, and the search for mechanisms by which they interact with the host to exert their therapeutic effects remains a key question currently being addressed. Considering their significant regenerative/therapeutic potential, research on mesenchymal stem cells (MSCs) has experienced an unprecedented advance in recent years, becoming the focus of extensive works worldwide to develop cell-based approaches for a variety of diseases. Initial evidence for the effectiveness of MSCs therapy comes from the restoration of dynamic microenvironmental homeostasis and endogenous stem cell function in recipient tissues by systemically delivered MSCs. The specific mechanisms by which the effects are exerted remain to be investigated in depth. Importantly, the profound cell-host interplay leaves persistent therapeutic benefits that remain detectable long after the disappearance of transplanted MSCs. In this review, we summarize recent advances on the role of MSCs in multiple disease models, provide insights into the mechanisms by which MSCs interact with endogenous stem cells to exert therapeutic effects, and refine the interconnections between MSCs and cells fused to damaged sites or differentiated into functional cells early in therapy.